ANALISIS MANAJEMEN PROGRAM PEER MENTORING BERBASIS ASRAMA DALAM MENINGKATKAN ACADEMIC HARDINESS MAHASISWA - Maria Amelia (SOSCIED, 2026)
This study aims to examine the management of the peer mentoring programme in enhancing academic hardiness (academic resilience) at St. Monika Hostel in Jayapura. The study used a qualitative approach with a descriptive method. Data was collected through interviews, observations, and document studies. Data validation was carried out using source and technique triangulation. The data collected were analysed using the flow model of Miles and Huberman, i.e. reduction of data, display of data, and conclusion/verification.  The results of the study show that the planning of the peer mentoring programme based on the hostel begins with the process of analysing the needs of the students, which forms the basis for the programme's objectives. This needs analysis is used to determine and organise mentors and mentees. The programme is implemented through activities such as assisting with homework, preparing for midterms/finals and reinforcing learning strategies and methods. The manager ensures that the programme is implemented properly by carrying out regular supervision of the learning support process. It is hoped that this peer mentoring programme will have a positive impact on the academic hardiness of students.